1975
DOI: 10.1002/dev.420080404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenobarbital given to pregnant mice on behavior of mature offspring

Abstract: Mature offspring of C57BL/6J mice (Mus musculus) injected daily with phenobarbital (40 mg/kg) for the last third of pregnancy differed from saline and untreated control animals on 3 measures of behavior. Offspring of phenobarbital treated animals had higher locomotor scores than controls during an open field activity test at 75 days of age. Male offspring were also tested on a 1-trial passive avoidance task and treated animals were found to be deficient. Finally, female offspring responded less than controls o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…For example, Middaugh et al (18) found retarded development of several neurologic reflexes in mice whose mothers received PB in midpregnancy. A defect in sexual mating behavior after neonatal exposure to the drug has been demonstrated by Clemens et al (3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Middaugh et al (18) found retarded development of several neurologic reflexes in mice whose mothers received PB in midpregnancy. A defect in sexual mating behavior after neonatal exposure to the drug has been demonstrated by Clemens et al (3).…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal phenobarbital exposure in rats reduces brain weight [6]. Mice exposed prenatally to phenobarbital have neuronal deficits, reduced brain weight, and impaired development of reflexes, open-field activity, schedule-controlled behavior, spatial learning, and cate-cholamine brain levels [7][8][9][10][11][12]. Gestational or neonatal exposure to phenytoin reduces brain weight [13,14], alters neuronal membranes in the hippocampus [15], delays neurodevelopment [16], and impairs spatial learning and motor coordination [17][18][19][20][21][22][23][24][25].…”
Section: Animal Studies On Behavioral Effects Of In Utero Aed Exposurementioning
confidence: 99%
“…In rats and mice, a large number of studies have demonstrated that prenatal phenobarbitone exposure can reduce fitter size (Middaugh et al 1975;Kuprys and Tabakoff 1981;McBride and Rosman 1984) and decrease birth weights (Kuprys and Tabakoff 1981 ;McBride and Rosman 1984). Prenatal and neonatal phenobarbitone administration can decrease subsequent growth (Middaugh et al 1975;Yanai etal.…”
Section: I)igc~onmentioning
confidence: 99%
“…In animals, prenatal or neonatal exposure to phenobarbitone can retard growth and reflex development, impair development of the brain and lead to subsequent dysfunctions of learning (Mural 1966;Brazelton 1970;Middaugh et al 1972Middaugh et al , 1975Diaz et al 1977;Yanai et al 1979Yanai et al , 1982Bergman etal. 1980;Hannah etal.…”
mentioning
confidence: 99%